Availability analysis and optimal inspection policy for systems with neglected down time. Issue 11 (3rd June 2019) - Qiu, Qingan; Cui, Lirong; Kong, Dejing
Abstract: Many practical systems are subject to neglected down time, i.e., if the down time is less than a given threshold, then the system can be considered as working during the down time. Otherwise, the system is considered as in the failure state. This paper investigates the availability and maintenance policy for inspected systems with neglected down time. The instantaneous and steady-state availabilities of the system are derived analytically. Furthermore, a maintenance model is developed to find the optimal inspection interval, T *, which minimizes the long-run average cost rate. Based on the developed maintenance model, the analytical properties of the optimal inspection policy are explored. Numerical examples on ventilator system calculating the availability and optimal inspection policy are given to illustrate the applicability of the proposed model.